KEMAMPUAN OLAH VOKAL SISWA MELALUI MODEL (STAD) DI KELAS XI IAI 1 MAN LUBUK ALUNG - Afri Rozi Fernandes; Syeilendra Syeilendra; Syahrel Syahrel (FBS Universitas Negeri Padang, 2012)
This research is Classroom Action Research (CAR), using a model of cooperative learning with the principal instrument is there searcher himself. Data collection tool is the observation sheet and test learning. Observation sheet used to determine the level of achievement of students after completion of the study.The purpose of this study is to describe the application of learning Cooperative Learning Model to improve if the vocal students in class XIIAI1 MAN Lubuk Alung. The study consisted of two cycles, and each cycle of the last meeting held on valuation. The researchers' findings of increased class XI student learning outcomesIAI1 after applying a model of cooperative learning in teaching practice if the vocals roman average initial value of69.2% to 80.94% with the thoroughness of individuals up to 100%. Kata kunci: abylity, vocal, modeling, stad.